REAKTUALISASI NILAI-NILAI PERSAUDARAAN PIAGAM MADINAH DALAM KEBUDAYAAN PELA GANDONG DI MALUKU - Sanusi Ulath; Ali Wafa (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2023)
This study examines how the interpretation of ukhuwah verses in the Qur'an in fostering unity and brotherhood that has relevance to the culture of Pela Gandong in Maluku as a reactualization of the values of brotherhood in the Medina charter. This research is qualitative research using library research methods and then analyzed descriptively with an anthropological approach. The results of this study show that Pela and Gandong culture is a representative of ukhuwah Islamiyah in essence, namely brotherhood based on Islamic values. Pela reflects brotherhood of humanity (ukhuwah insaniyah) and Gandong reflects brotherhood established by family and national ties (ukhuwah wathaniyah wa an-nasab). The values of brotherhood in pela gandong culture are mutual help, providing a sense of security between others, understanding each other's characteristics